Regulation of the electricity industry in Bolivia: Its impact on access to the poor, prices and quality - Antonio Bojanic; Michael Krakowski (Hamburg Institute of International Economics (HWWA), 2003)
This paper takes stock with the results of utility privatization in Bolivia. This paper deals with the process of structural reforms in this country and the specific results that have to date been accomplished in the electricity industry. It is mostly interested in exploring whether the reformation of this industry contributed to lessen poverty levels and whether in light of the obtained results, a reversal or a continuation of the reform process should take place. The paper shows that coverage of electricity users has grown faster in urban areas ever since the establishment of regulation. Although it is not argued that regulation has caused the increase in electricity consumers, the data does show that a comparatively faster urban growth rate of users takes place after 1995. In this sense, it seems plausible that regulation of the electricity industry has indeed lessen poverty levels in urban Bolivia by making this utility more accessible to larger segments of the urban population. The same cannot be said, however, about rural Bolivia. The results show that coverage has remained about the same in the last 10 years, with no discernible improvement after the transformation of the industry in 1995. When rural Bolivia is divided into income groups, the data shows that some of the poorest groups have indeed experienced a decline in coverage during the regulation period, which sheds doubts about the purportedly positive effects that structural changes in this industry were to have in the livelihoods of the poorest people in the country. Alternative ways which may improve the poverty reduction outcome of electricity regulation are explored.
Keywords: O54; O20; L51; 330; Regulation; Poverty Reduction; Bolivia; Elektrizitätspolitik; Armutspolitik; Städtische Armut; Ländliche Armut; Bolivien